2021
DOI: 10.3389/fonc.2021.620361
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Kynurenine 3-Monooxygenase Expression in Colorectal Cancer

Abstract: Colorectal cancer (CRC) is a leading cause of cancer-related deaths. Because of the lack of reliable prognostic and predictive biomarkers for CRC, most patients are often diagnosed at a late stage. The tryptophan–kynurenine pathway plays a crucial role in promoting cancer progression. Kynurenine is considered an oncometabolite in colon cancer, and its downstream metabolites are also associated with CRC. Kynurenine 3-monooxygenase (KMO), a pivotal enzyme that catalyzes kynurenine metabolism, is essential for se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…In our previous study, the overexpression of KMO was correlated with malignancy by promoting cell proliferation and metastasis in TNBC cells [11]. Elevated KMO levels also led to a poor prognosis in patients with TNBC [15], colorectal cancer [43], and HCC [16]. Taken together, the malignant role of the KMO was reported, which aligns with our findings from using numerous bioinformatics tools.…”
Section: Discussionsupporting
confidence: 90%
“…In our previous study, the overexpression of KMO was correlated with malignancy by promoting cell proliferation and metastasis in TNBC cells [11]. Elevated KMO levels also led to a poor prognosis in patients with TNBC [15], colorectal cancer [43], and HCC [16]. Taken together, the malignant role of the KMO was reported, which aligns with our findings from using numerous bioinformatics tools.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, high surface expression of KMO was detected in cytosol and on the cell membranes of breast cancer tissue specimens, indicating its potential as a treatment target for TNBC [139]. A recent study investigated the correlation between upregulated KMO activity and poor clinical outcomes in colorectal cancer (CRC) patients and demonstrated that KMO inhibition suppressed CRC cell proliferation in vitro [140]. On analysing KMO enzyme expression in 120 matched HCC tissue samples, Jin et al showed that the expression of the KMO enzyme is significantly elevated in HCC tumour tissue compared to adjacent normal liver tissue.…”
Section: Kmomentioning
confidence: 99%
“…There are three main hypotheses with regard to the relevance of active tryptophan catabolism through the KP in the tumor microenvironment [59]: first, overexpression of active IDO from malignant cells may deplete the tryptophan pool, thus inhibiting lymphocyte proliferation and abrogating the anti-tumor immune response [34]; second, active KP metabolism could favor the formation of tryptophan derivates that inhibit the proliferation of cytotoxic lymphocytes and induce their death [35,36]; and third, the KP can lead to the constant formation of NAD + , a coenzyme involved in metabolic and signaling pathways, contributing to the suitability of malignant cells [60]. In accordance with this, KMO is the pivotal enzyme in the KP that leads to NAD + synthesis [61] and is related to poor prognosis in several cancers [58,[62][63][64].…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, blocking the KMO surface with a KMO polyclonal antibody reduces migration and invasion of MDA-MB-231 cells [57]. Additionally, inhibition of KMO activity represses colorectal cancer cell migration, invasion, and tumor sphere formation [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation